ANALISA PENGUNAAN BARCODE UNTUK ADMINISTRASI INCOMING DAN OUTGOING PADA TERMINAL KARGO DI BANDAR UDARA INTERNASIONAL ZAINUDDIN ABDUL MADJID LOMBOK - Ian Rafi Ramadhan; Ariyono Setiawan; Setyo Hariyadi Suranto Putro (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
it was found that the recording of incoming and outgoing data at the Lombok International Airport was less than optimal because it was still using manual recording by operators, both administrative and field operators, and the results of the questionnaire also showed that 80% of cargo service users thought that cargo still used manual recording. The less than optimal use of information technology, both from interviews and questionnaire results, 80% of service users stated that information technology had not been used. Satisfactory However, the conditions in the field could not be applied due to constraints on equipment and resources at the location when the observations were carried out.